2015
DOI: 10.1016/j.prevetmed.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Testing Eurasian wild boar piglets for serum antibodies against Mycobacterium bovis

Abstract: Animal tuberculosis (TB) caused by infection with Mycobacterium bovis and closely related members of the M. tuberculosis complex (MTC), is often reported in the Eurasian wild boar (Sus scrofa). Tests detecting antibodies against MTC antigens are valuable tools for TB monitoring and control in suids. However, only limited knowledge exists on serology test performance in 2-6 month-old piglets. In this age-class, recent infections might cause lower antibody levels and lower test sensitivity. We examined 126 wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…In Spain, the Eurasian wild boar is regarded as the key wildlife MTC maintenance host; its infection prevalence rates are >50% in Mediterranean areas that have dense wild boar populations ( 6 ). Up to one third of wild boar piglets might become infected during their first 6 months of life ( 7 ). In half of MTC-infected wild boars, generalized lesions develop that affect the lungs, particularly in juveniles (12–24 months of age).…”
mentioning
confidence: 99%
“…In Spain, the Eurasian wild boar is regarded as the key wildlife MTC maintenance host; its infection prevalence rates are >50% in Mediterranean areas that have dense wild boar populations ( 6 ). Up to one third of wild boar piglets might become infected during their first 6 months of life ( 7 ). In half of MTC-infected wild boars, generalized lesions develop that affect the lungs, particularly in juveniles (12–24 months of age).…”
mentioning
confidence: 99%
“…Negative samples of this group of juvenile animals should be assayed. Furthermore, the difference of sensitivity found among animals of different ages when INgezim tests were used could be explained due to the fact that in adult wild boar, antibody production is closely related to infection status/lesion severity, whereas lesions can appear in juvenile wild boar exposed to a great burden of M. bovis , but, due to their younger age, the production of MPB83/70 specific antibodies has not reached a detectable level yet; as already shown by Che' Amat et al, .…”
Section: Resultsmentioning
confidence: 93%
“…LFAs have been described to analyse elephant, cervid and non‐human primate sera, with sensitivities ranging from 79% in elk to 100% in elephants (Lyashchenko, Gortazar, Miller, & Waters, ; Lyashchenko et al, ). This LFA has also been tested in wild boar serum, providing high specificity and sensitivity (Che' Amat et al, ), but with the limitation that it only detects IgGs (Boadella et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this observation has been reported in wild boar and may reflect the time dependence of this chronic disease (Santos et al., ). However, other studies in wild boar have shown the opposite outcome with juveniles or sub‐adults being at higher risk or no difference in infection rates between age groups (Boadella et al., ; Che’ Amat et al., ). More research is needed in our specific case.…”
Section: Discussionmentioning
confidence: 95%
“…Serological assays have been shown to be an accurate tool for assessing bTB prevalence in European wild boar (Aurtenetxe et al., ; Boadella et al., ; Che’ Amat et al., ). Our results demonstrate that the indirect PPD ELISA is a useful tool to estimate prevalence and evaluate epidemiologic risk factors for M. bovis infection in warthogs in Africa.…”
Section: Discussionmentioning
confidence: 99%